The Effect of Auditor Ethics, Motivation and Competence on Auditor Performance - Apriani Harahap, Nur Fitri; Ade Budi Setiawan; Maria Magdalena Melani (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to explore the influence of ethics, motivation, and competence on auditor performance at the Bogor City Inspectorate. The background of this study is based on the phenomenon where auditors do not always comply with the applicable code of ethics, and the supervision system requires further evaluation. This study adopts a quantitative method, using a questionnaire as a data collection instrument distributed to 40 internal auditors at the Bogor City Inspectorate. The variables analyzed include auditor ethics, motivation, and competence as independent variables, and auditor performance as the dependent variable. The results of the study indicate that ethics, motivation, and competence simultaneously have a significant influence on auditor performance, as indicated by the results of the F test with a calculated F value of 40.410, greater than the F table of 2.866, and a significance of 0.000. Partially, ethics and competence have a positive influence on auditor performance, while motivation has a negative influence. This study concludes that improving ethics, directed motivation, and adequate competence are very important in improving auditor performance in the government environment, especially at the Bogor City Inspectorate.